Transformasi Menuju Industri 4.0: Perspektif Praktisi Mengenai Kebutuhan Transisi Digital dengan Penerapan Papan Visualisasi Manajemen pada Lantai Produksi - Amran, Ali; Arifuddin; Asril, Akmil (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
The development of Industry 4.0 has pushed manufacturing firms to accelerate information flow, improve decision accuracy, and reorganize communication on the shop floor. This study aims to analyze practitioners’ perspectives on the need for digital transition through the use of management visualization boards. A qualitative case study design was applied through 12 semi-structured interviews, 9 observations of production briefings, and a review of 18 supporting documents. The findings show that management visualization boards still function as the main medium of daily operational communication because they help teams review targets, discuss problems, and determine corrective actions quickly. Manual boards were considered superior for briefing flexibility, especially for marking issues, drawing arrows, and making short sketches during discussion. However, manual data updates were time-consuming, created duplicate recording, and made problem histories difficult to trace. Digital boards were seen as neater, easier to monitor, and more supportive for reading trends, but they could not fully replace manual boards because they did not yet support spontaneous discussion and not all data were automatically integrated. Practitioners mainly expected faster data updates, lower administrative burden, stored action histories, and cross-shift and cross-unit information access. These results indicate that digital transition should proceed carefully in production environments overall.